Developing supplementary reading materials for tenth-graders of English language and literature program - Agustin Susilowati; Hasti Robiasih (Journal of English Language and Pedagogy, 2021)
The objectives of this study were (1) to develop supplementary reading material for grade X students of English Language and Literature program (ELLP) and (2) to describe the efficacy of the developed supplementary reading material. This research was categorized as Educational Research and Development (R&D) and it employed six steps among the ten proposed by Borg and Gall's model (1983). Those were (1) conducting need analysis, (2) constructing the course grid, (3) developing the first draft of the material (4) getting the expert judgment, (5) revising and writing the final draft of the material, and (6) conducting field testing. The instruments used in this research were questionnaires and interview guidelines. Two types of questionnaires were used to collect the data. The first questionnaire used to obtain the data for the needs analysis was administered to grade X students of ELLP of SMAN 11 Yogyakarta. The second questionnaire used to obtain the data about the appropriateness of the materials was administered to the experts. The materials were designed and based on the frame work proposed by Task Based Instruction (Willis, 1996). The findings showed 1) the development of supplementary reading materials was to fulfill the students' need; the result of need analysis was used to develop the reading materials (2) the efficacy of the developed supplementary reading material helped students to enhance their reading comprehension skills and to achieve the goal of learning reading. Based on the expert judgment, the mean score of all aspects of the two developed units, in the scales of 1-4 was 3.93 which was in the range of 3.50 < x â‰¤ 4.00 and could be categorized as Very Good. It can attract students to be actively involved in the teaching and learning process. Furthermore, it provides additional learning resource for students to learn reading.